Rest as a Bodily Right: A Mubādalah Analysis of Manbaus Sa‘adah by Faqihuddin Abdul Qadir - Alindah, Lutfiyah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the concept of the body’s right to rest from a gender-just Islamic perspective through a mubādalah reading of Manbaus Sa‘adah by Faqihuddin Abdul Qadir. Using a qualitative library research method, the analysis focuses on the Qur’an, hadith, classical scholarly views, and feminist Islamic theories by figures such as Amina Wadud and Asma Barlas. The findings reveal that rest is recognized as a divine blessing and a basic human need equally for men and women, grounded in the maqāṣid al-syarī‘ah principles of ḥifẓ al-nafs (protection of life) and ḥifẓ al-‘aql (protection of intellect). Manbaus Sa‘adah offers a counternarrative to patriarchal interpretations by framing rest not as a luxury but as a right to be respected, facilitated, and shared equitably within the household. This study contributes to inclusive Islamic discourse and has practical implications for promoting gender-equitable domestic practices that humanize women in both private and public spaces.